Analysis Of The Potential For Beef Cattle Development With An Extensive System In The Savana Fields Of Pekat District, Dompu Regency, West Nusa Tenggara Province - Andi Setiawan; Sumartono; Inggit Kentjonowaty (Jurnal Ternak, 2025)
The purpose of this study was to determine the profile of beef cattle farming in Padang Savana, Pekat District, Dompu Regency and also to analyze the potential for developing beef cattle farming in Padang Savana, Pekat District, Dompu Regency. The method used in this study was a qualitative descriptive approach. This research was implemented from September 1, 2024, to September 30, 2024 , taking place in Padang Savana, Pekat District, Dompu Regency . The results of this study show that the savannah in Pekat District, Dompu Regency has an area of 2000 hectares with a total population of 46,177 animals consisting of cattle, goats, horses, and buffalo spread across 12 villages. The total carrying capacity of the savannah in Pekat District, Dompu Regency is 154,922 animals. The SWOT analysis of the savannah in Pekat District, Dompu Regency consists of Strengths of the grazing fields which have a land area of 2000 hectares , the grazing fields which have the largest population in Dompu Regency , the grazing fields which have the largest contribution to the livestock economy in Dompu Regency. Weaknesses of the grazing fields which are only covered by grass with low nutritional content , the grazing fields which have a drinking water crisis for livestock in the dry season , suboptimal disease prevention management. Opportunities for planting superior grass seeds that have high nutritional content to meet the needs of livestock green fodder , procurement of irrigation systems or drilling water sources , sustainable grazing programs . Threats for attacks animal cruelty to livestock , less than optimal security , conversion of land into agricultural land, causing conflict between livestock breeders and farmers.